Energy Crisis and Energy Conservation Measures of the Thai Government: A Policy Analysis to Strengthen National Energy Security - Bunpum, Nattachai (Thai Social Science Journal, 2026)
This article aims to analyze the global energy crisis and its impact on Thailand, examine the Thai government's energy-saving measures, and propose policy recommendations to strengthen national energy security. The study employs document analysis and policy analysis based on reports from government agencies, international organizations, and recent developments in the global energy market. The findings indicate that the global energy crisis in 2026 has been driven by multiple factors, including geopolitical tensions in the Middle East—particularly conflicts involving Iran—volatility in global energy markets, and imbalances between energy supply and demand. These factors have led to significant increases in global oil and natural gas prices, placing considerable pressure on countries that rely heavily on imported energy resources. Thailand’s energy structure remains largely dependent on fossil fuels and imported energy, particularly crude oil and liquefied natural gas (LNG). This dependence makes the country vulnerable to fluctuations in global energy markets. In response, the Thai government has implemented several energy-saving measures, including reducing energy consumption in government agencies, promoting work-from-home arrangements, improving energy management in public buildings, diversifying energy import sources, and promoting alternative energy such as biofuels and renewable energy. However, addressing the energy crisis in the long term requires structural adjustments in national energy policy. This study proposes key policy recommendations, including diversifying energy sources to reduce dependence on imports, increasing the share of renewable energy in the national energy mix, and improving energy efficiency across all sectors. These strategies are expected to enhance Thailand’s energy security and reduce vulnerability to global energy market volatility in the future.